Higher Education Financing and Curriculum Development in Indonesian Islamic Higher Education Institutions (IHEIs) - Neli Alawiah; Ali Masrur; Dadang Darmawan (Journal of Economicate Studies, 2026)
Despite extensive discussions on higher education financing and curriculum reform, limited attention has been given to how financial capacity shapes curriculum development in Indonesian Islamic Higher Education Institutions (IHEIs). This study addresses this gap by examining the nexus between higher education financing and curriculum development within the context of Indonesian Islamic higher education. Employing a qualitative library research design, the study analyzes scholarly literature, policy documents, and relevant empirical studies to identify patterns, challenges, and policy implications associated with financing and curriculum practices. The findings reveal that the availability, diversity, and sustainability of funding significantly influence curriculum innovation through investments in academic infrastructure, faculty development, digital learning resources, and quality assurance systems. However, disparities in institutional resources and funding structures among IHEIs generate uneven capacities for curriculum renewal and implementation. This study contributes to the literature by providing an integrated perspective on the interaction between financial resources and curriculum development in Islamic higher education and by highlighting the importance of equitable and sustainable financing policies to strengthen institutional adaptability and educational quality in Indonesia.